SINERGI STAKEHOLDER DALAM MENANGANI ANCAMAN PENYELUNDUPAN NARKOBA DI PROVINSI ACEH - Dhimas Rudy Hartanto; Artha C. Rosevina Anak Ampun; Endyka Triono Dachi; Surya Wiranto; M. Adnan Madjid (Universitas Halu Oleo, 2021)
Narcotics is a substance that is very dangerous when consumed by the body. One of the areas affected by the spread of narcotics is Aceh Province. Drug smuggling transactions are carried out by sea by transferring narcotics from one ship to another. The Aceh Provincial National Narcotics Agency (BNNP) has a duty to prevent, eradicate the abuse and illicit trafficking of narcotics. The results in this study are that the Aceh BNNP strategy in stopping drug smuggling with the experience of arresting the bandar is quite heavy because the perpetrators use sophisticated information technology. The act of smuggling drugs by sea is a collaboration between smugglers and fishermen. Enforcement and rehabilitation activities as well as prevention activities have been carried out through visual publics, social media, and others. The government has coordinated with neighboring countries considering that drug smuggling can already be called a proxy war. Drug trafficking by sea is a serious threat that must be dealt with seriously. BNN also synergizes with the Maritime Security Agency and Customs and Excise to jointly fortify Indonesian sea from drug attacks. Several agencies such as Tuha Peut, Tuha Lapan, and Panglima Laot were well embraced to assist the drug trafficking process in Aceh.